A randomised control trial and cost-consequence analysis to examine the effects of a print-based intervention supported by internet tools on the physical activity of UK cancer survivors. (June 2019) - Webb, J.; Fife-Schaw, C.; Ogden, J.
Abstract: Objective: The objective of this study was to evaluate the effectiveness of a print-based intervention supported by Internet tools at improving physical activity in cancer survivors compared with a standard letter recommendation. Prediagnosis physical activity and self-efficacy were hypothesised to predict physical activity improvement. Study design: Waiting list randomised control trial and cost-consequence analysis. Methods: Adult cancer survivors who could become physically active without prior medical approval were randomised to receive either a print-based intervention supported by Internet tools (intervention, n = 104) or a standard letter recommendation (control, n = 103). Physical activity was assessed at 12 weeks with maintenance assessed at 24 weeks in the intervention arm. The number needed to treat was calculated, and a cost-consequence analysis completed. Results: Participants in receipt of a print-based intervention supported by Internet tools improved their physical activity by 36.9% over 12 weeks compared with 9.1% in the control arm. Physical activity was maintained at 24 weeks in the intervention arm. A total of 6.29 cancer survivors needed to receive the intervention for one cancer survivor to improve their physical activity over a standard letter recommendation. Intervention delivery cost £8.19 per person. Prediagnosis physical activity and self-efficacy did not predict physical activity improvement. Conclusion: A print-based intervention supported by Internet tools offers a promising low-cost means to intervene to improve physical activity in cancer survivors. The study was registered with the International Standard Randomised Controlled Trials Number registry (registration number: 66418871), and ethical approval was received from the University of Surrey (reference: UEC/2017/023/FHMS). Highlights: The Move More Pack significantly improves physical activity in cancer survivors. A total of 6.29 persons need to receive the intervention for one physical activity improvement. Intervention delivery costs £8.19 per person. Print and Internet interventions can potentially raise activity in cancer survivors. There is potential for further research and development in this area.